Avaliação do atendimento antirrábico humano pós exposição, associado a acidentes com cães, no município de Belo Horizonte, no período de 2011 e 2012 - Karine Chaves Cabral (2015)
Rabies is a viral zoonosis with a high death toll, close to 100%. In every treatment of animal attack a full anamnesis must be performed using a Human anti-rabies assistance file to collect every information regarding the case and indicate the proper prophylactic treatment. The classification of de incident/attack, light or severe, will depend on the characteristics of the wound, such as: which part of the body, depth, length and number of lesions. The prophylactic study of human rabies contributes to a better orientation regarding the use of anti-rabies vaccines and saline and enables the understanding of the circumstances as a base for the definition of strategies to prevent, control and evaluate human rabies. The goal was to analyze the anti-rabies human treatment post initial exposure and possible incompatibilities with the health ministry protocol in dog attacks in the district of Belo Horizonte in 2011 e 2012. An exploratory analysis was made in the anti-rabies treatment files of the information system of injury notification (SINAN NET 4.0). The treatments indicated by the health centers with the norms of the health ministry were compared. The frequent characteristics of treatments due to dog attacks were: regarding exposure, 93% were due to bites and 5.2% due to scratches; regarding part of body, 35.5% in lower members and 33.1% in hands/feet; regarding number of wounds, 62% were single wounded; regarding type of wound, 65.8% were superficial; regarding animal conditions, 85% were healthy animals; 83.4% of the animals were observed; regarding treatment, the most frequent was observation and vaccine (57.3%) and less prevailing was treatment dismissal (1.43%). The first anti-rabies prophylactic treatment post exposure was inadequate in 32.71% of the prophylactic conducts. The number of prophylactic treatments performed in human beings was very high, 75.71% of people attacked. In all treatments 21.22% of prophylactic indications were considered excessive and 11.48% insufficient. The surveillance system presents flaws and its necessary to correct them so that information regarding the closing of the cases can be conclusive. An analyses and enhancement of the file of anti-rabies treatment is recommended and standardized country wide and also the constant training of health professionals involved in the process.